Analysis of COVID-19’s Effects on the Incidence of Chronic Respiratory Symptoms in KPK - Anwar Ul Haq, Muhammad Asif Khan, Imran Qadir Khattak, Farhan Zeb, Hameed Ullah, Muhammad Awais (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Pakistan has a high prevalence of chronic respiratory disorders, including bronchial asthma and chronic obstructive pulmonary disease (COPD). Objectives: Finding the effect of COVID-19 on chronic respiratory disease in Pakistan is the study’s key goal. Material and methods: From February 2021 to December 2021, this cross-sectional research was carried department of pulmonology at HMC hospital Peshawar A specified To differentiate between the COVID-19 era and the period preceding it, a set of criteria in the form of a questionnaire was applied. Results: A total of 157 participants contributed to the data set. Patients who tested positive for COVID 19 were additionally asked about their experiences with respiratory co morbidities. More than a third of respondents mentioned COPD as a co morbidity; many also mentioned bronchial asthma, ILD, and tuberculosis (TB). Conclusion: COVID-19 would certainly increase chronic respiratory disorders in Khyber Pakhtunkhwa. The pandemic might increase respiratory disorders, strain health systems, and cost people impacted. Increase public health awareness and ensure chronic respiratory illness patients get proper treatment and resources to address these issues. To decrease the pandemic’s effect on Khyber Pakhtunkhwa’s population, early respiratory disease identification and treatment techniques are needed. Keywords: Analysis , Respiration, COVID-19 Patients, COPD